2012
DOI: 10.1103/physrevstab.15.092001
|View full text |Cite
|
Sign up to set email alerts
|

New method to improve the accuracy of quench position measurement on a superconducting cavity by a second sound method

Abstract: Quench is a common phenomenon in a superconducting cavity and often limits the accelerating gradient of the cavity. Accurate location of the quench site, typically located at a material or geometrical defect, is the key to improve the cavity accelerating gradient. Here, the second sound propagation in liquid helium II is used to detect the quench location on the cavity. The technique is relatively convenient and complements the traditional temperature mapping which measures the ''prequench'' temperature rise o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…For our further studies on quench detection, it is important and challenging to understand the effect of thermodynamics in cavity surface made of niobium and the transition of heat propagation from the niobium to the superfluid helium. In [19], it was observed that heat could first propagate along the cavity surface and then later excite an entropy wave in the superfluid helium. In particular, in experiments since the speed of propagation is faster in the niobium than in the superfluid helium, the measured travel time at an OST is smaller.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our further studies on quench detection, it is important and challenging to understand the effect of thermodynamics in cavity surface made of niobium and the transition of heat propagation from the niobium to the superfluid helium. In [19], it was observed that heat could first propagate along the cavity surface and then later excite an entropy wave in the superfluid helium. In particular, in experiments since the speed of propagation is faster in the niobium than in the superfluid helium, the measured travel time at an OST is smaller.…”
Section: Resultsmentioning
confidence: 99%
“…However, in practice, they have experienced difficulties in exactly locating a quench. For instance, when the real wave velocity is higher than the theoretical one, the radii are too small to have an intersection point on the cavity surface, see [7,19,20,21] and the references therein. The size of the quench is another potential source of inaccuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Such premature signals have been experimentally observed by nearly all the laboratories which have used second sound sensors to localize a quench in a superconducting cavity [8,10,11,14,15]. Different hypothesis have been envisaged to explain this difference, and will be discussed later in this paper.…”
Section: Ost Measurements At 17 Kmentioning
confidence: 93%
“…Using a velocity to describe the processes in niobium was originally meant as an example calculation [35]. It is based on simulated results in [15]. This approach was shown to match real systems surprisingly well as shown in [16].…”
Section: A Probing Fast Signal Propagation In Niobiummentioning
confidence: 99%
See 1 more Smart Citation